Bold Basics of Social Studies in Elementary School - Marhamah, Fitrah; Shofwah, Aqilah Nadya; Ramadhani, Citra Suci; Zahra, Khaira Laini; Lutfiah, Zahra Meida; Khairunnisa, Khairunnisa (LPPPIPublishing, 2025)
Social Studies in elementary schools plays an important role in shaping students' character, knowledge, and social skills from an early age. This article examines the philosophical, sociological, pedagogical, and psychological foundations underlying the development of social studies in elementary schools through a literature review. The research was conducted by reviewing 20 recent academic sources (2020–2025) relevant to elementary school social studies education. The results show that the philosophical foundation determines the scope and objectives through ontological, epistemological, and axiological aspects. The sociological foundation highlights the relationship between the social studies curriculum and social dynamics and community needs. The pedagogical foundation focuses on learning strategies that are appropriate to the developmental characteristics of students. The psychological foundation ensures that learning is in line with children's cognitive, affective, and socio-emotional development. These findings emphasize the importance of a comprehensive approach based on the four foundations of education to realize contextual and meaningful social studies learning that supports the achievement of national education goals.